Antibiotic Susceptibility of Bacteria Isolated from Open Fracture Grade III Presenting to Dr. Soetomo General Academic Hospital Surabaya - Wibisono, Raden Taufan Mulyo; Utomo, Dwikora Novembri; Widodo, Agung Dwi Wahyu ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: Open fractures are a typical case in the orthopedics field. Infection in an open fracture can cause osteomyelitis. An antibiotic susceptibility testing of patient specimen bacteria with open fractures aimed to determine suitable antibiotic agents with which to treat the infectious diseases caused by these bacteria.Methods: This research is a descriptive study to assess antibiotic susceptibility in cases of open fracture grade III in Dr. Soetomo General Academic Hospital, Surabaya. Total sampling was performed on the microbiological culture results of patients diagnosed with open fracture grade III after debridement from October 2018 to September 2019. The identification of the microbes was based on Gram-positive and Gram-negative categories, and the classification was based on susceptibility to antibiotics, whether sensitive, intermediate, and resistant.Results: The examination of the data from the microbiological culture results of patients with a diagnosis of open fracture grade III after debridement from October 2018 to September 2019 in Dr. Soetomo General Hospital Surabaya resulted in 56 research subjects who met the criteria. Acinetobacter baumannii was the most common bacterial species found in the microbiological examination of patients with open fractures, at 15.84%. Cefazoline and ceftriaxone showed low susceptibility. Levofloxacin showed a relatively good value of susceptibility against both Gram-positive and negative bacterial groups.Conclusion: The antibiotic susceptibility pattern of bacteria from specimens in open fracture grade III patients in Dr. Soetomo General Academic Hospital Surabaya varies between each species of bacteria isolate.